2013
DOI: 10.3934/mbe.2013.10.279
|View full text |Cite
|
Sign up to set email alerts
|

Using wavelet denoising and mathematical morphology in the segmentation technique applied to blood cells images

Abstract: Accurate image segmentation is used in medical diagnosis since this technique is a noninvasive pre-processing step for biomedical treatment. In this work we present an efficient segmentation method for medical image analysis. In particular, with this method blood cells can be segmented. For that, we combine the wavelet transform with morphological operations. Moreover, the wavelet thresholding technique is used to eliminate the noise and prepare the image for suitable segmentation. In wavelet denoising we dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 23 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…The High-Pass filter that forms the wavelet function generates approximations A for each decomposition level. Details of D (Mallat, 1999) (Boix & Cantó, 2013) are provided by the complementary low-pass filter representing the scaling function. This algorithm is referred to as subband coding.…”
Section: Discrete Wavelet Transform (Dwt)mentioning
confidence: 99%
“…The High-Pass filter that forms the wavelet function generates approximations A for each decomposition level. Details of D (Mallat, 1999) (Boix & Cantó, 2013) are provided by the complementary low-pass filter representing the scaling function. This algorithm is referred to as subband coding.…”
Section: Discrete Wavelet Transform (Dwt)mentioning
confidence: 99%
“…In fact, Gauss de-noising has attracted the attention of a large number of researchers, and many de-noising algorithms have been presented that achieved good results in many research fields [7,8]. However, the Gauss de-noising is still a problem [8] and its performance is not ideal in real applications.…”
Section: Introductionmentioning
confidence: 99%
“…These have a great impact on the visual system of an apple harvesting robot, and make it difficult to recognize targets [5,6]. Through the subtraction image method, it is showed that the noise in night vision images is generally mixed noise, and the Gauss noise is found to be the main noise among them [7].…”
Section: Introductionmentioning
confidence: 99%